1998
DOI: 10.2494/photopolymer.11.237
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Fluorescence and Thermal Properties of Transparent Polyimides Based on 2,3,5-Tricarboxycyclopentylacetic Acid Dianhydride.

Abstract: Ultraviolet/visible absorption spectra and fluorescence spectra of transparent polyimides derived from 2,3,5-tricarboxycyclopentylacetic acid dianhydride (TCAAH) with an aromatic diamine, 4,4'-diaminodiphenylmethane (DPM), a fluorinated diamine, 2,2 bis(4-diaminodiphenyl)hexafluoropropane (6FdA), and an alicyclic diamine, 4,4'-diaminodicyclohexylmethane (DCHM) were investigated, as well as their thermal properties. All polyimide films derived from TCAAH showed high transparency in the visible region, i. e., no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The DIMA/CBDA PI based on alicyclic dianhydride showed excitation peak at 355 nm and emission peak at 401 nm with a relatively small Stokes shift of 3231 cm −1 . CBDA monomer composed of alicyclic structure showed weak electron acceptor property and thus shorter wavelength due to the inhibition of the interchain CT. 37 The Stokes shifts of the aromatic PIs which are significantly larger than those of the alicyclic-based PI and the relatively broaden nature of the fluorescent emission spectra clearly indicate the existence of enhanced CT interactions in the PI network, which is typical for aromatic PIs. In contrast, these CT interactions are considerably weakened in the DIMA/CBDA PI film due to the absence of CT interactions between aromatic moieties and the presence of bulky alicyclic diamines.…”
Section: Resultsmentioning
confidence: 94%
“…The DIMA/CBDA PI based on alicyclic dianhydride showed excitation peak at 355 nm and emission peak at 401 nm with a relatively small Stokes shift of 3231 cm −1 . CBDA monomer composed of alicyclic structure showed weak electron acceptor property and thus shorter wavelength due to the inhibition of the interchain CT. 37 The Stokes shifts of the aromatic PIs which are significantly larger than those of the alicyclic-based PI and the relatively broaden nature of the fluorescent emission spectra clearly indicate the existence of enhanced CT interactions in the PI network, which is typical for aromatic PIs. In contrast, these CT interactions are considerably weakened in the DIMA/CBDA PI film due to the absence of CT interactions between aromatic moieties and the presence of bulky alicyclic diamines.…”
Section: Resultsmentioning
confidence: 94%
“…It also can be found in Figure S3 that PICu films exhibited obvious excitation wavelength-dependent emission with a change of excitation wavelength from 200 to 225 nm, while PIZn films did not show the same excitation dependence. Generally, the excitation wavelength dependence of fluorescence emission was first found by Horie’s group, and it was reported that the excitation wavelength dependence of liquid-crystalline polyester (LCP) was related to the form or distribution of multiple emission sites based on different degrees of overlap between mesogenic biphenyl moieties. Thus, the excitation dependence of PICu might due to the interaction of Cu 2+ with multiple atoms on benzimidazole, indicating the coordination form of point-to-face style . In addition, Zn 2+ ions in PIZn with point-to-point multi-coordination only formed coordinate bonds with N atoms (CN) in benzimidazole moieties, whose kind of ligand atom was single, and the PIZn films did not exhibit excitation dependence in Figure S3b, further indicating the point-to-face coordinate form of PICu films.…”
Section: Resultsmentioning
confidence: 99%